Strategy of the Public Relations Team of LLDIKTI Region III in Enhancing Public Services in the Digitalization Era - Alif, Sisin Nastasya Ametha; Zain, Herlina Muzanah (ARISTO, 2026)
This study aims to identify how the Public Relations (PR) team of LLDIKTI Region III designs strategies to improve public services in the digitalization era by launching the SIL@T application. This research employs the theory of Parasuraman, Zeithaml, and Berry (1998), which consists of five indicators that serve as the foundation for developing service quality improvement strategies: Tangibles (physical form), Reliability, Responsiveness, Assurance, and Empathy. The study uses a qualitative descriptive method by conducting direct observations of the occurring phenomena. The findings indicate that LLDIKTI Region III has met the five indicators of service quality improvement, both in terms of infrastructure and direct services, as well as technology-based services through the launch of the SIL@T application. Moreover, the services provided, whether through face-to-face interactions or the SIL@T application, have received positive feedback from users.